The introvert's guide to the workplace : concrete strategies for bosses and employees to thrive and succeed - Orozco, Thea (Skyhorse Publishing, 2020)
This book is every working introvert's handbook that they can reference throughout their career for guidance on tricky or draining situations and motivation to enlist the power of their inner introvert to succeed.Learn about how to combat interview anxiety, make meaningful connections at networking events, be heard and noticed at meetings or on the stage, overcome importer syndrome, become an effective leader with your introvert strengths and more!